PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS KURIKULUM 2013 PADA MATERI POKOK SEGIEMPAT MELALUI PENERAPAN PEMBELAJARAN BERDASARKAN MASALAH - Fadriati Ningsih; Sakur '; Atma Murni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to develop mathematics learning device that are Lesson Plan (LP) and Students Worksheet (SW) based curriculum 2013 on subject quadrilateral through the application of problem based learning. This research and development use development model by Borg and Gall modified by Sugiyono (2008). Development is done through the following steps: (1) potentials and problems; (2) data collection; (3) design products: (4) validation; (5) revision; (6) small group trial; (7) revision; (8) large group trial; and (9) revision. At the stage of potentials and problems, the researchers conducted a needs analysis concluded Core Competence (CC) - Basic Competence (BC) analysis, characteristics of students analysis, and materials analysis. Then, researcher collect the necessary materials to design learning device. Learning device that had been developed then validated by three validators and revised based on the input from validators. The valid learning device then tested in two stages, the small group trial with subjects are eight students of class VII-4 SMP Negeri 3 Tambang and large group trial with subjects are 29 students of class VII-4 SMP Negeri 3 Tambang. Based on the data analysis and discussion can be concluded that the mathematics learning device based curriculum 2013 on subject quadrilateral through the application of problem based learning are valid with an average value for the LP is 3.79 and the average value for SW is 3.82, and is practical to use by learners class VII.Keywords: Mathematics Learning Device, Curriculum 2013, Research and Development, Problem Based Learning, Quadrilateral